Implementation of Pascal's Law Learning Media with a Scientific Approach to High School Physics Learning - Ziyad Fadhlan Nabil; Vivi Mardian; Bagus Putra Ramadhan; Dadi Rusdiana (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Physics learning is inseparable from experiments. Some teachers have not been able to provide experimental tools in schools. One of the materials that requires experimental tools is Pascal's Law. The solution provided is in the form of developing a Pascal's law experimental tool using the R & D method. The development is using the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. The aim of this research is to investigate the results of the implementation of the Pascal's law experimental tool. Data collection instruments with pre-test, post-test, student worksheet, and student response questionnaires. The sample was taken from one class of 20 class 11 physics students at West Java. The questions on the pre-test and student worksheet totaled 7 items and 10 questions respectively. The student response questionnaire consisted of four aspects, namely aspects of ease of use, attractiveness, efficiency, and suitability of the material. Overall, the indicators totaled 11 items which were distributed using Google Form to students. The results of the analysis show that there is a change in the results of the students' pre-test and post-test with an N-Gain of 0.24 (low category). The results of the student response questionnaire analysis are 79.51%. This indicates that the tools developed are practical and can be used in learning physics, especially Pascal's law. Future research is expected to be able to see a comparison of student learning outcomes using the Pascal's law experimental tool directly with a virtual experiment with PhET.